ANALISIS TIPE KEPRIBADIAN FLEGMATIS TOKOH SARWONO PADA NOVEL HUJAN BULAN JUNI KARYA SAPARDI DJOKO DAMONO - Nurmalasari Nurmalasari; Erlina Zahar; sujoko sujoko (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this research is to describe the types of phlegmatic personality in Sarwono character in the novel Hujan Bulan Juni by Sapardi Djoko Damono which refer to eleven aspects. That eleven aspects of phlegmatic personality are flexibel, courtesy, calm, quiet, pleased, administrative ability, peaceful, sosialization, having a lot of friends, good listener. This research isdescriptive qualitative. Based on the result of the analysis, it can be concluded that the types of phlegmatic personality in the novel Hujan Bulan Juni by Sapardi Djoko Damono are flexibel, courtesy, calm, quiet, patience, pleased, administrative ability, peaceful, sosialization, having a lot of friends, and good listener. From that elevent aspects of phlegmatic personality, the most utterances found in the novel Hujan Bulan Juni by Sapardi Djoko Damono are pleased, flexiblem good listener. These phlegmatic aspects represent the character of Sarwowno as good and wise person.in the novel Hujan Bulan Juni karya Sapardi Djoko Damono.Key Word: personality, phlegmatic, novel